Study on Sound Absorption Properties of Coconut Coir Fibre Reinforced Composite with Added Recycled Rubber - Mahzan, S.; Ahmad Zaidi, A.M.; Arsat, N.; M. Hatta, M. N.; Ghazali, M. I.; Mohideen, S. Rasool (International Journal of Integrated Engineering, 2010)
Sound pollutions have become worsen and creating concerns for many peoples. Conventionally, expensive sound absorption materials are employed to control noise disturbances. However, recent developments on natural fibres have created interest for researchers especially for acoustics application purposes. This paper investigates the viability of coconut coir added with recycled rubber to be implemented as sound absorption panel. The composite is constructed at prescribed percentages of fillers and polyurethane as resin. The two-microphone method was applied to obtain the acoustic properties of the samples. The samples were also tested for physical properties such as density and porosity, as well as the microstructures. The results demonstrate good acoustics performances and highlight the potential of the coconut coir reinforced with recycled rubber as the sound absorption panel.